Effectiveness of nuclear deterrence against Russia - Kostrzewa-Zorbas Grzegorz (2022)
The objective is to answer three research, policy, and strategy questions: 1. Is and will be the NATO and US strategy of nuclear deterrence effective against Russia? 2. Can the strategy of nuclear deterrence as the supreme guarantee of the security of NATO have a lasting public acceptance in the member states? 3. Is it necessary to complement the NATO and US strategy of nuclear deterrence with another, also strong but different, guarantee of security?